2016
DOI: 10.1371/journal.pbio.1002420
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Context and Attention on Spiking Activity in Human Early Visual Cortex

Abstract: Here we report the first quantitative analysis of spiking activity in human early visual cortex. We recorded multi-unit activity from two electrodes in area V2/V3 of a human patient implanted with depth electrodes as part of her treatment for epilepsy. We observed well-localized multi-unit receptive fields with tunings for contrast, orientation, spatial frequency, and size, similar to those reported in the macaque. We also observed pronounced gamma oscillations in the local-field potential that could be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 82 publications
15
84
1
Order By: Relevance
“…3e). These results are similar to a variety of electrophysiological measurements (50,58,84,(113)(114)(115)(116)(117)(118).…”
Section: Recurrent Amplification Effective Time Constant Onset Transupporting
confidence: 87%
See 2 more Smart Citations
“…3e). These results are similar to a variety of electrophysiological measurements (50,58,84,(113)(114)(115)(116)(117)(118).…”
Section: Recurrent Amplification Effective Time Constant Onset Transupporting
confidence: 87%
“…All of these results, except for one, are commensurate with experimental observations that oscillation amplitudes and frequencies depend systematically on stimulus contrast, size, and spatial pattern (31,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86), and that oscillations are linked to normalization (31,72). Like the simulation results, oscillation amplitudes have been observed to increase with stimulus contrast and size, oscillation frequencies increase with stimulus contrast, and oscillations are smaller for plaids than for gratings (and even smaller for stimuli composed of multiple components, also predicted by the model).…”
Section: Oscillations Depend On Stimulus Contrast and Sizesupporting
confidence: 85%
See 1 more Smart Citation
“…The speed at which the enhanced neuronal activity spreads over the target curve is comparable to the speed with which human observers trace the curve27. Furthermore, it was recently shown that neuronal firing rates in the human visual cortex elicited by target curves are higher than those elicited by distractors, just as is the case in monkey visual cortex30. Thus, the curve-tracing task is useful to study the top-down influences related to perceptual organization and object-based attention in the visual cortex25.…”
mentioning
confidence: 91%
“…This will require human single-neuron latency estimates in higher cortical visual areas, which have not been performed to date. Notably, recordings from early visual areas V2/V3 in humans indicate that the response latencies in these areas do not differ between monkeys and humans (Self et al, 2016). This raises the possibility that local processing in higher areas specific to humans is responsible for this substantial increase in response latency.…”
Section: Discussionmentioning
confidence: 99%